Adsorption and biodegradation functions of novel microbial embedding polyvinyl alcohol gel beads modified with cyclodextrin: a case study of benzene. Issue 15 (3rd July 2019) - Wu, Nan; Li, Xiaofang; Huang, Guoshuai; Pan, Peng; Wang, Chang; Liu, Xinyuan; Zeng, Ming
ABSTRACT: A novel microorganism embedding material was developed to enhance the benzene removal through adsorption and biodegradation, by introducing β-cyclodextrin (CD) to traditional polyvinyl alcohol gel beads. Results show that the optimal ratio of sucrose/benzene was 1.25 for co-metabolism biodegradation of benzene, and the maximum exogenous microbial respiration rate was 260.13 mgO2 /(gVSS h) for gel beads with CD. The positive effects of CD on benzene removal mainly resulted from the adsorption characteristics of CD as well as the stimulation of CD on microbial activity. Adsorption tests indicate that CD addition increased the adsorption function of gel beads to benzene with its dispersion coefficient of 5.1 × 10 −7 cm 2 /s. Respiration tests show that gel beads with CD possessed the highest maximum specific exogenous respiration rates. Moreover, a high-throughput sequencing analysis confirms that CD addition could obviously enhance microbial diversity with domain microbial of Zoogloea (17.0%). Finally, microbial embedding gel beads could remove certain benzene after lyophilization and storage for one month. Overall, the novel microbial embedding gel beads modified with CD (a favorable additional agent to traditional embedding materials) have been proved as an efficient method for removing benzene under suitable sucrose/benzene ratio.